2008
DOI: 10.1016/j.disc.2007.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Thue type problems for graphs, points, and numbers

Abstract: A sequence S =s 1 s 2 . . . s n is said to be nonrepetitive if no two adjacent blocks of S are the same. A celebrated 1906 theorem of Thue asserts that there are arbitrarily long nonrepetitive sequences over the set {0, 1, 2}. This result is the starting point of Combinatorics on Words-a wide area with many deep results, sophisticated methods, important applications and intriguing open problems.The main purpose of this survey is to present a range of new directions relating Thue sequences more closely to Graph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 49 publications
1
56
0
Order By: Relevance
“…More than 100 years ago Thue [9] proved that there are nonrepetitive sequences of arbitrary length using only the symbols 1, 2, and 3. This result has been extended in many directions and a recent survey of Grytczuk [5] collects a substantial number of such results. In this paper we consider an extension to graph theory suggested by Alon et al [2].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…More than 100 years ago Thue [9] proved that there are nonrepetitive sequences of arbitrary length using only the symbols 1, 2, and 3. This result has been extended in many directions and a recent survey of Grytczuk [5] collects a substantial number of such results. In this paper we consider an extension to graph theory suggested by Alon et al [2].…”
Section: Introductionmentioning
confidence: 89%
“…The answer to Question 1 is still open, but we provide some evidence suggesting an affirmative answer. At the Budapest workshop in honor of Miklós Simonovits' 60th birthday, Grytczuk suggested replacing planar by outerplanar as a first point of attack (see also [5]). …”
Section: Question 1 Is There a Constant K Such That Every Planar Gramentioning
confidence: 98%
“…The smallest k such that H has a non-repetitive k-coloring is called the Thue number π(H) of H [Thue 1906]. Alon et al [2002] showed via the LLL that π(H) ≤ O( (H) 2 ), where is the maximum degree of any vertex in H. This was followed by many additional works [Alon and Grytczuk 2008;Bresar et al 2007;Currie 2005;Grytczuk 2008;Kündgen and Pelsmajer 2008;Schaefer and Umans 2002]. However, no efficient construction is known till date, except for special classes of graphs such as complete graphs, cycles and trees.…”
Section: Applications That Avoid All Bad Eventsmentioning
confidence: 99%
“…Nonrepetitive colourings have recently been widely studied; see the survey [15]. A number of graph classes are known to have bounded nonrepetitive chromatic number.…”
Section: Nonrepetitive Graph Colouringsmentioning
confidence: 99%